CEP55 is a determinant of cell fate during perturbed mitosis in breast cancer - Murugan Kalimutho; Debottam Sinha; Jessie Jeffery; Katia Nones; Sriganesh Srihari; Winnie C Fernando; Pascal HG Duijf; Claire Vennin; Prahlad Raninga; Devathri Nanayakkara; Deepak Mittal; Jodi M Saunus; et al. (EMBO Molecular Medicine, 2018)
Abstract The centrosomal protein, CEP55, is a key regulator of cytokinesis, and its overexpression is linked to genomic instability, a hallmark of cancer. However, the mechanism by which it mediates genomic instability remains elusive. Here, we showed that CEP55 overexpression/knockdown impacts survival of aneuploid cells. Loss of CEP55 sensitizes breast cancer cells to anti‐mitotic agents through premature CDK1/cyclin B activation and CDK1 caspase‐dependent mitotic cell death. Further, we showed that CEP55 is a downstream effector of the MEK1/2‐MYC axis. Blocking MEK1/2‐PLK1 signaling therefore reduced outgrowth of basal‐like syngeneic and human breast tumors in in vivo models. In conclusion, high CEP55 levels dictate cell fate during perturbed mitosis. Forced mitotic cell death by blocking MEK1/2‐PLK1 represents a potential therapeutic strategy for MYC‐CEP55‐dependent basal‐like, triple‐negative breast cancers.